Barrettův bůh: Problémy reprezentacionalistického přístupu ve studiu náboženství - Daniel Musil (AntropoWebzin, 2017)
Justin L. Barrett in his 2008 article “Why Santa Claus is not a god” argued that a collection of a few basic representational content features can explain why a god concept can become the centre of widespread religious beliefs and practices. In this article, I demonstrate the ways in which Barrett’s representational model fails in defence of his main hypothesis, and I use his model as an example to show the limits of similar approaches in the cognitive science of religion.